2008
DOI: 10.1016/j.febslet.2008.12.019
|View full text |Cite
|
Sign up to set email alerts
|

The C‐terminal of CysM from Mycobacterium tuberculosis protects the aminoacrylate intermediate and is involved in sulfur donor selectivity

Abstract: Edited by Richard CogdellKeywords: Cysteine synthase Protein structure Tuberculosis Dormancy Oxidative stress a b s t r a c t A new crystal structure of the dimeric cysteine synthase CysM from Mycobacterium tuberculosis reveals an open and a closed conformation of the enzyme. In the closed conformation the five carboxy-terminal amino acid residues are inserted into the active site cleft. Removal of this segment results in a decreased lifetime of the a-aminoacrylate reaction intermediate, an increased sensitivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 41 publications
0
13
1
Order By: Relevance
“…This change occurred within 20 min, and the resulting spectrum corresponds with that of the enzyme-bound PLP. Compared with the results from similar experiments using O-acetylserine sulfhydrylases (36), the lifetime of the ␣-aminoacrylate intermediate in DcsD is obviously shorter than that in normal O-acetylserine sulfhydrylases. This may be another reason for the high K m value of DcsD toward L-OAS.…”
Section: In Vitro D-cs Synthesiscontrasting
confidence: 63%
“…This change occurred within 20 min, and the resulting spectrum corresponds with that of the enzyme-bound PLP. Compared with the results from similar experiments using O-acetylserine sulfhydrylases (36), the lifetime of the ␣-aminoacrylate intermediate in DcsD is obviously shorter than that in normal O-acetylserine sulfhydrylases. This may be another reason for the high K m value of DcsD toward L-OAS.…”
Section: In Vitro D-cs Synthesiscontrasting
confidence: 63%
“…Based on E. coli, three enzymes were identified that may have cysteine desulfhydrase activity in S. enterica: CysK, CysM, and STM1557 (34% identical to E. coli MalY) (27). These PLP-dependent enzymes generate pyruvate, hydrogen sulfide, and ammonia from cysteine, and it was plausible that these reactions would proceed through a 2AA intermediate (29,46,47). Deletions of cysK, cysM, and stm1557 were generated by gene replacement (39), and strains that contained each mutation alone or in combination with a ridA mutation were constructed.…”
Section: Resultsmentioning
confidence: 99%
“…Similar collapsing of the active site upon PLP-α-aminoacrylate intermediate formation is observed in structures determined for homologues CysK1 and CysM from M. tuberculosis . 25,56 Loss of the phosphate group upon formation of the stable PLP-α-aminoacrylate intermediate from OPS precluded direct structural identification of residues involved in OPS specificity. However, the active site of SbnA-AA revealed three residues: Arg132, Tyr152, and Ser185 are in close proximity to the β-carbon of the α-aminoacrylate intermediate (Figure 3B), and all three residues were shown to be involved in formation of the intermediate.…”
Section: Discussionmentioning
confidence: 99%